Bad feelings, feeling bad: the affects of Asian-Indigenous coalition. Issue 2 (3rd April 2019) - Diabo, Gage Karahkwí:io
ABSTRACT: This article theorizes the affective forms that Asian-Indigenous alliances might take, using examples from contemporary Canadian film and literature as a cultural testing ground. Building on the efforts of scholars like Rita Wong, Larissa Lai, and Malissa Phung to trace a literary genealogy of Asian-Indigenous relations in Canada, the article first considers the structures of feeling which bolster efforts towards coalition-building between Asian settlers and First Nations. Rather than extending an optimistic or redemptive model, the article suggests that negative affect (or, what Sianne Ngai calls "ugly feelings") ought to be taken seriously as both an unavoidable presence and a potential catalyst in and for active solidarity. The article then analyzes Sto:lo author Lee Maracle's short story "Yin Chin" and Peter Blow's documentary film A Village of Widows with an eye towards how bad feelings underpin the narrative calls to action in both texts. The article concludes by considering the role that bad feeling can and does play in terms of inter-referencing practices among cultural and historical scholars.